PM.98 Maternal Renal Outcomes Following Pregnancy Complicated by Chronic Kidney Disease Stages 3–5. (26th April 2013) - Webster, L; Webster, P; Lightstone, L
Abstract : Objectives: To establish the effect of pregnancy on deterioration of renal function in women with Chronic Kidney Disease (CKD) stages 3–5 attending the renal antenatal clinic. Methods: All women with excretory renal dysfunction (creatinine >110 µmol/L or eGFR < 60 ml/min) prior to pregnancy were identified from the Obstetric-Renal database. Outcomes assessed included; decline in renal function during pregnancy (defined as 25% increase in serum creatinine), persistent decline in renal function six months post-partum and time to renal replacement therapy. Results: 49 women (57 pregnancies) with CKD stages 3–5 were identified with sufficient data for analysis. Diabetes mellitus was the underlying diagnosis in nine (16%) pregnancies. 18 (32%) pregnancies were complicated by chronic hypertension. 11 (19%) pregnancies occurred in women with previous renal transplant. 21% of women had >1 g/day proteinuria prior to pregnancy. 11 (22%) women had a decline in renal function in pregnancy. Decline in renal function at 6 months post-partum was present in a total of 16 (33%) women. Predictors of significant decline in renal function included; pre-pregnancy creatinine mean 222 µmol/L in those with decline in function and 138 µmol/L in those without (p = 0.0015), and significant proteinuria >1 g/day present in 87.5% (p = 0.02). Nine (18%) women went on to need renal replacement therapy (RRT), four within a year of delivery. Mean time to RRT was 23 months. Conclusions: Pregnant women with CKD 3–5 are at high risk of deterioration in renal function during and after pregnancy. Level of creatinine prior to pregnancy and significant proteinuria are risk factors for decline in function.